A Novel Transcriptome Integrated Network Approach Identifies the Key Driver lncRNA Involved in Cell Cycle With Chromium (VI)-Treated BEAS-2B Cells - Zheng, Pai; Kang, Yulin; Han, Shuo; Feng, Huimin; Ha, Feizai; Long, Changmao; Zhou, Di; Hu, Guiping; Chen, Zhangjian; Wang, Zengmiao; Wang, Tiancheng; Jia, Guang (Frontiers in Genetics, 2021)
Hexavalent chromium [Cr(VI)] is a well-known occupational carcinogen, but the mechanisms contributing to DNA damage and cell cycle alternation have not been fully characterized. To study the dose-response effects of Cr(VI) on transcription, we exposed BEAS-2B cells to Cr(VI) at concentrations of 0.2, 0.6, and 1.8 μmol/L for 24 hours. Here, we identified 1,484 differentially expressed genes (DEGs) in our transcript profiling data, with the majority of differentially expressed transcripts being downregulated. Our results also showed that these DEGs were enriched in pathways associated with the cell cycle, including DNA replication, chromatin assembly, and DNA repair. Using the differential expressed genes related to cell cycle, a weighted gene co-expression network was constructed and a key mRNA-lncRNA regulation module was identified under a scale-free network with topological properties. Additionally, key driver analysis (KDA) was applied to the mRNA-lncRNA regulation module to identify the driver genes . The KDA revealed that ARD3 (FDR=1.46×10−22), SND1 (FDR=5.24×10-8), and lnc-DHX32-2:1 (FDR=1.43×10−17) were particularly highlighted in the category of G2/M, G1/S, and M phases. Moreover, several genes we identified exhibited great connectivity in our causal gene network with every key driver gene, including CDK14, POLA1, lnc-NCS1-2:1, and lnc-FOXK1-4:1 (all FDR<0.05 in those phases). Together, these results obtained using mathematical approaches and bioinformatics algorithmics might reveal potential new mechanisms involved in the cytotoxicity induced by Cr.